2007
DOI: 10.1063/1.2755964
|View full text |Cite
|
Sign up to set email alerts
|

Stable, high efficiency gyrotron backward-wave oscillator

Abstract: Stability issues have been a major concern for the realization of broadband tunability of the gyrotron backward-wave oscillator (gyro-BWO). Multimode, time-dependent simulations are employed to examine the stability properties of the gyro-BWO. It is shown that the gyro-BWO is susceptible to both nonstationary oscillations and axial mode competition in the course of frequency tuning. Regions of nonstationary oscillations and axial mode competition are displayed in the form of stability maps over wide-ranging pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…25 Previous studies have revealed some essential properties of the gyro-BWO, and the stable operation regimes were also demonstrated by the theoretical analysis 25 and experiments. 10 However, there are some unresolved issues needed to be further studied for getting a more in-depth understanding of the intriguing electrodynamical system. For example, the effective lengths of the gyro-BWO in the linear and nonlinear regimes, respectively, are drastically different, such that it is difficult to establish a fixed relationship between the start oscillation threshold and the nonstationary oscillation threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Previous studies have revealed some essential properties of the gyro-BWO, and the stable operation regimes were also demonstrated by the theoretical analysis 25 and experiments. 10 However, there are some unresolved issues needed to be further studied for getting a more in-depth understanding of the intriguing electrodynamical system. For example, the effective lengths of the gyro-BWO in the linear and nonlinear regimes, respectively, are drastically different, such that it is difficult to establish a fixed relationship between the start oscillation threshold and the nonstationary oscillation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding wave equation is then given by Dðdx; k m À i@ z ÞAðzÞ ¼ 0; (10) which, noting that @Dðdx;k m Þ @k m ¼ 0, yields the following eigenmode equation for AðzÞ, i.e., h Dðdx; k m Þ À 1 2…”
mentioning
confidence: 99%
“…Gyro-devices are fast-wave sources and traditionally are based on a smoothbore waveguide, rather than a slow-wave structure (SWS) that greatly limits the power handling capability of the THz sources. The gyro-backward wave oscillator (gyro-BWO) [5] and gyro-traveling wave amplifier (gyro-TWA) [6] are fast wave devices which can operate using higher order modes where the electrons are bunched in the azimuthal direction and do not rely on a SWS to longitudinally bunch the electrons in the beam.…”
Section: Introductionmentioning
confidence: 99%
“…The gyrotron backward-wave oscillator ͑gyro-BWO͒, which features continuous frequency tunability 3 attracts more and more attention from various applications, such as electron spin resonance, plasma diagnostics, and sensitivity enhancement of nuclear magnetic resonance using dynamic nuclear polarization. [4][5][6][7] Recently, the high efficiency and the broadband tunability of gyro-BWO were achieved at Ka-band 3,8 and X-band, 9,10 respectively. However, little literature has so far been reported at W-band.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ␣ declines sharply with either the increase in the magnetic field B 0 or the decrease in the beam voltage V b , which significantly lowers the efficiency and results in narrow bandwidth. 3,8,19 Based on the above considerations, there is a pressing need to develop a MIG with high and constant ␣ as well as low velocity spread for a W-band or a terahertz gyro-BWO.…”
Section: Introductionmentioning
confidence: 99%